Tailoring Heat Treatment Strategies to Enhance Corrosion Resistance and Mechanical Performance of Low-Carbon Steel in Marine Environment - Basiru Philip Aramide; Tamba Jamiru; Taoreed Adesola Adegbola; Abimbola Patricia Idowu Popoola (Science, Engineering and Technology)
This study examines the impact of various heat-treatment processes on the corrosion resistance and mechanical properties of low-carbon steel, specifically for maritime applications. The carbon steel samples were evaluated at 750°C and subsequently cooled using two methods: normalizing and quenching. Alterations in the microstructure, hardness, and corrosion resistance were examined using contemporary techniques such as X-ray diffractometry (XRD), optical microscopy, wear testing, and electrochemical analysis in simulated seawater. The primary findings indicate that quenching enhances the hardness (from 170 to 404 HV) and corrosion resistance of steel by producing martensite, with a corrosion rate of 8.44 × 10⁻⁵ mm/year; however, this process also increases the brittleness of the steel. The process of normalizing results in a microstructure characterized by ductility, comprising both ferrite and pearlite phases. This structure exhibited a moderate level of resistance to corrosion, with a corrosion rate of 0.001018 mm/year. Conversely, the integration of normalizing with quenching results in a well-balanced microstructure, enhancing the material's toughness and corrosion resistance, with a lowest corrosion rate of 6.12 × 10⁻⁵ mm/year. Testing under saline conditions revealed that the quenched samples exhibited superior performance, highlighting the significance of cooling rates in enhancing material properties. This study demonstrates the importance of heat treatment in reducing the damage caused by saltwater corrosion of carbon steel. It also provides useful information on how to ensure that marine infrastructure is more durable and functions better.